Penerapan Metode Permainan Ular Tangga dalam Meningkatkan Prestasi Belajar Matematika Materi Bangun Ruang Kubus Siswa Kelas V SDN Ngemplak Simongan 01 Semarang - Cicilia Yantini; Mei Fita Asri Untari; Ikha Listyarini (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Indonesian student mathematics achievement in International not good. One reason is the learning of mathematics at the elementary level. Many teachers teach mathematics in a conventional manner. The learning method is not in accordance with the psychological and cognitive students. Learning mathematics less provide excitement and creativity. The aims of this research are to find out the effect of using snake and ladder game to increase mathematics learning outcomes in cubical lesson of the fifth grade students of Ngemplak Simongan 01 elementary school Semarang. Learning by educational games is learning with real act so making abstracts concept of mathematics subject are given more contextual and can settle to the student’s memory. This game be expected can improve student’s motivation to learn mathematics subject with operations of integers and help students to learn independently. The research method used in this study is qualitative approach to answer the formulation of the problems. The population and samples of this study were 12 students of fifth-grade in Ngemplak Simongan 01 elementary school. There were test and non test instruments used in this study. The test instruments consisted of validated and reliability 25 questions. Non test instuments consisted of observations and interviews. The test results showed that the overall of educational game snakes and ladders on the mathematics subject grade V of elementary school is proper or good to use. The result showed that there were significant effects between the used of snake and ladder games to mathematic learning outcomes in the cubical lesson. The snake and ladder games were modification games which had purpose helping students to solve the difficulties in memorize mathematic cubical formulas. Teachers could use the snake and ladder educative games to teach cubical lesson so that students could make it easier to study mathematic.